RISE: an open-source architecture for interdisciplinary and reproducible human–robot interaction research - Groß, André; Schütze, Christian; Brandt, Mara; Wrede, Britta; Richter, Birte (Frontiers in Robotics and AI, 2023)
In this article, we present RISE -a Robotics Integration and Scenario-Management Extensible-Architecture for designing human-robot dialogues and conducting Human-Robot Interaction (HRI) studies. In current HRI research, interdisciplinarity in the creation and implementation of interaction studies is becoming increasingly important. In addition, there is a lack of reproducibility of the research results. With our presented open-source architecture, we want to address these two topics. Therefore, we discuss the advantages and disadvantages of various existing tools from different sub-fields within robotics. Requirements for an architecture can be derived from this overview of the literature, which (1) supports interdisciplinary research, (2) allows reproducibility of the research, and (3) is accessible to other researchers in the field of HRI. With our architecture, we tackle these requirements by providing a Graphical-User-Interface (GUI), which explains the robot behavior and allows introspection into the current state of the dialogue. Additionally, it offers controlling possibilities to easily conduct Wizard-of-Oz (WoZ) studies. To achieve transparency, the dialogue is modeled explicitly and the robot behavior can be configured. Furthermore, the modular architecture offers an interface for external features and sensors and is expandable to new robots and modalities.